(untitled) (Ha Noi, 2003)
The Ba upgrade English language teaching methodology course was developed through the english teacher training project . The project was supported throughout by the Ministry of Education and Training. The process of developing the course took three years. It consisted of conducting a needs analysis of lower secondary school teachers; training the writers in materials development and the delivery of learner center, task based training, writing, piloting and rewriting the modules; linking the tasks to the new Tieng anh textbook series and developing the trainer's notes
Giảng dạy các kỹ năng ngôn ngữ,Phương pháp dạy học Tiếng Anh
Keywords: English and language,Tiếng Anh; Study and teaching,Foreign speakers,Dạy và học,Những người nói tiếng nước ngoà